El llemosinisme valencià a la darreria del segle XIX - Rafanell, August (Caplletra. Revista Internacional de Filologia, 2015)
As this paper tries to show, the association between the terms Catalan and llemosí, traditionally used in an indiscriminate way when mainly referring to Catalan, was clearly revised and corrected by the middle of the 19th century both in Catalonia and the Balearic Islands, but not so in Valencia, where its persistence can be seen as the clear expression of an outstanding form of local particularism vis à vis the raising linguistic Catalanism.